Flight dynamics principles - Cook, M. V. (Arnold ; J. Wiley, 1997)
Flight dynamicists today need not only a thorough understanding of the classical stability and control theory of aircraft, but also a working appreciation of flight control systems and consequently a grounding in the theory of automatic control. In this text the author fulfils these requirements by developing the theory of stability and control of aircraft in a systems context. The key considerations are introduced using dimensional or normalised dimensional forms of the aircraft equations of motion only and through necessity the scope of the text will be limited to linearised small perturbation aircraft models. The material is intended for those coming to the subject for the first time and will provide a secure foundation from which to move into non-linear flight dynamics, simulation and advanced flight control. Placing emphasis on dynamics and their importance to flying and handling qualities it is accessible to both the aeronautical engineer and the control engineer. Emphasis on the design of flight control systems Intended for undergraduate and postgraduate students studying aeronautical subjects and avionics, systems engineering, control engineering Provides basic skills to analyse and evaluate aircraft flying qualities.